2018
DOI: 10.1152/ajpheart.00121.2018
|View full text |Cite
|
Sign up to set email alerts
|

PTEN inhibitor VO-OHpic attenuates inflammatory M1 macrophages and cardiac remodeling in doxorubicin-induced cardiomyopathy

Abstract: Doxorubicin (Doxo) is an effective agent commonly used in cancer therapeutics. Unfortunately, Doxo treatment can stimulate cardiomyopathy and subsequent heart failure, limiting use of this drug. The role of phosphatase and tensin homolog (PTEN) in apoptosis has been documented in Doxo induced cardiomyopathy (DIC) and heart failure models. However, whether direct inhibition of PTEN attenuates apoptosis, cardiac remodeling, and inflammatory M1 macrophages in DIC model remains elusive. Therefore, the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…In another study, Hadi et al reported that treatment with vitamin E and telmisartan significantly reduces infiltration of monocytes into the heart, thereby reducing the cardiac inflammatory response, relieving DOX-induced cardiac injury and improving cardiac dysfunction [ 37 ]. We and other researchers have reported that DOX treatment promotes imbalance between M1 macrophages and M2 macrophages in mice, and aggravation of this imbalance further aggravates cardiac injury and cardiomyocyte apoptosis [ 7 , 38 ]. These results suggest that DOX-induced immune cell activation plays an important role in myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Hadi et al reported that treatment with vitamin E and telmisartan significantly reduces infiltration of monocytes into the heart, thereby reducing the cardiac inflammatory response, relieving DOX-induced cardiac injury and improving cardiac dysfunction [ 37 ]. We and other researchers have reported that DOX treatment promotes imbalance between M1 macrophages and M2 macrophages in mice, and aggravation of this imbalance further aggravates cardiac injury and cardiomyocyte apoptosis [ 7 , 38 ]. These results suggest that DOX-induced immune cell activation plays an important role in myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy has been shown to mitigate the in ammatory response with exercise (53,64), induce leukopenia/cytopenia (19), and disrupt cardiacmacrophage in ltration (65). To the best of our knowledge, this is the rst study to demonstrate that chemotherapeutic 5FU has deleterious effects on immune cell abundance in otherwise healthy uninjured skeletal muscle.…”
Section: Discussionmentioning
confidence: 82%
“…Pathologically, immune-related adverse events in the setting of ICIs treatment are largely characterized by the infiltration of macrophages into the tissue, causing injury 10 . Recent data suggest the involvement of macrophage polarization in cardiovascular diseases, such as chemotherapy-related cardiac injury 11 . Under some condition, monocytes travel to the site of injury and undergo differentiation into either proinflammatory M1 macrophages or antiinflammatory M2 macrophages 12 .…”
Section: Introductionmentioning
confidence: 99%